Stool Microbiota in Infants Receiving Extensively Hydrolyzed Formula, Amino Acid Formula, or Human Milk Through Two Months of Age (FS04-07-19). (13th June 2019) - Kok, Car Reen; Brabec, Bradford; Chichlowski, Maciej; Harris, Cheryl; Moore, Nancy; Wampler, Jennifer; Vanderhoof, Jon; Hutkins, Robert
Abstract: Objectives: Infant feeding practices play a central role in development of gut microbiome and community structure. Our goal was to test the hypothesis that diets with intact or extensively hydrolyzed proteins or free amino acids may differentially affect the intestinal microbiota composition and immune reactivity. Methods: This multicenter, double-blind, controlled, parallel-group, pilot study compared stool microbiota outcomes from Baseline (1-7 days of age) up to 60 days of age in healthy term infants. Infants received mother's own milk (assigned to human milk [HM] reference group) ( n = 25) or were randomized to receive one of two infant formulas: amino-acid based (AAF; n = 25) or extensively hydrolyzed cow's milk protein (EHF; n = 28). Neither study formula included added Lactobacillus rhamnosus GG. DNA was extracted (Baseline, Day 30, Day 60), 16S rRNA genes were amplified and sequenced (Illumina MiSeq), and exact amplicon sequence variants (ASV) were assigned using the DADA2 model. Alpha (Shannon, Simpson, Chao1) and beta diversity (Bray Curtis distance) and differential abundance in taxa were analyzed. Relative ASV enrichment (Baseline vs Day 60) was visualized using heat maps and taxa abundance was analyzed by DESEq2 in R (ver 3.4.3). Results: Complete stool data (all study time points) were available for 49 participants. Baseline alpha diversity measures were similar among groups. The HM group remained stable throughout the study. However, alpha diversity measures by Day 60 were significantly higher for AAF and EHF groups compared to HM. Significant group differences in beta diversity at Day 60 were detected ( P < 0.001); AAF and EHF clustered more closely compared to the HM group. Relative Bifidobacterium abundance increased over time and was significantly enriched at Day 60 in the HM group (Figure, A). At Day 60, a significant increase in members of Firmicutes was detected for AAF and EHF groups; a decrease in Enterobacteriaceae ( Escherichia ) was observed for EHF (Figure, B). Conclusions: Distinct patterns of early neonatal microbiome establishment were demonstrated for infants receiving mother's own milk compared to amino acid-based or extensively hydrolyzed protein infant formulas. Providing different sources of dietary protein early in life may impact gut microbiome development. Funding Sources: Mead Johnson Pediatric Nutrition Institute. Supporting Tables, Images and/or Graphs: